Pengendalian Kualitas Pelayanan melalui Analisis GAP dengan Instrumen Servqual (Studi di Unika Widya Mandala Surabaya) - Widyarini, Lydia Ari; Supriharyanti, Elisabeth (Jurnal Widya Manajemen & Akuntansi, 2003)
The strong competitiveness in higher education make the Widya Mandala Surabaya Catholic University (WMSCU) has to evaluate the operational process. So it could take the information which used to control the operational process through the strategic for adapted itself with the fluctuatif changes. This research is descriptive-evaluative used the gap analysis (Parasuraman-et al, 19S6. 1he-re're Jive variables: tangtbte, reliability, responsiveness, assurance and empathy. Then umbero f to^pl"t are 477f rom the WMSCUs tudents,le cturers,e mployeesa nd management' \he resultst iere're gap I (froi employees ide), gap 2,3,4,A tt of the the Sapsc awe gap 5 which shows the dtlferences betwien studints perceive service quality with the services that student hqve. According this evaluation, we could meet the causes of problem and the solution.